Parathyroid hormone-related protein in lower vertebrates - Danks, J. A. (2014)
1. Parathyroid hormone-related protein (PTHrP) is an important mediator of humoral hypercalcaemia of malignancy in humans. Normal human subjects have very low levels of PTHrP in their circulation. 2. Parathyroid hormone-related protein has recently been demonstrated in high levels in the circulation and tissues of the sea bream and the dogfish, leading to the hypothesis that PTHrP may be a 'classical' hormone in fish. 3. Immunohistochemistry and in situ hybridization were performed to investigate the evolutionary history of PTHrP. Tissues were examined from a number of lower vertebrates, including lungfish, lamprey and several species of bony and cartilaginous fish. Parathyroid hormone-related protein was localized to the skin and to kidney tubules in all animals studied. In the developing lungfish, PTHrP was observed in the notochord, developing brain and skeletal muscle layers. These results suggest that PTHrP is of ancient origin and has a basic and fundamental function in vertebrates.